The role of elective neck dissection in high‐grade parotid malignancy: A hospital‐based cohort study. (29th August 2019) - Harbison, R. Alex; Gray, Alan J.; Westling, Ted; Carone, Marco; Rodriguez, Cristina P.; Futran, Neal D.; Cannon, Richard B.; Houlton, Jeffrey
Abstract : Objectives/Hypothesis: The role of elective neck dissection (END) in patients with clinically N0 (cN0), high‐grade parotid carcinoma is unclear. The objective of this study was to assess the association between END and survival in patients with cN0, high‐grade parotid carcinoma. Study Design: Retrospective, multicenter cohort study. Methods: A review of hospital‐based cases from the National Cancer Data Base was performed. Participants included patients diagnosed with cN0, high‐grade parotid cancer between January 1, 2004 and December 31, 2013. The primary exposure was receipt of neck dissection. Secondary exposures included receipt of adjuvant radiation and/or chemotherapy. Univariate and multivariate survival analyses were performed. Unadjusted and adjusted survival estimates were determined. Results: Overall, 1, 547 patients were included, with a median follow‐up time of 48 months. END did not have a statistically significant effect on 3‐year survival (3‐year: 69.9%, 95% confidence interval [CI]: 67.2 to 72.6). Survival at 3‐years among those not receiving END was 66.1% (95% CI: 62.7 to 69.5). Parotidectomy and adjuvant radiotherapy had the strongest effect on mortality. There was no difference in 3‐year survival among patients who underwent parotidectomy and adjuvant radiation stratified by receipt of END nor did END have a statistically significant effect on survival in mucoepidermoid carcinoma, adenocarcinoma, high‐risk histology, high T stage, or academic center treatment subgroups. Conclusions: END did not have a statistically significant effect on survival among cN0 patients with high‐grade parotid cancer when taking into account receipt of adjuvant therapy and confounding. The role of END on survival and locoregional control remains to be further elucidated in prospective studies. Level of Evidence: 4 Laryngoscope, 130:1487–1495, 2020